2023
DOI: 10.1038/s41586-023-06308-w
|View full text |Cite
|
Sign up to set email alerts
|

A binary pulsar in a 53-minute orbit

Abstract: Spider pulsars are neutron stars that have a companion star in a close orbit. The companion star sheds material to the neutron star, spinning it up to millisecond rotation periods, while the orbit shortens to hours. The companion is eventually ablated and destroyed by the pulsar wind and radiation1,2. Spider pulsars are key for studying the evolutionary link between accreting X-ray pulsars and isolated millisecond pulsars, pulsar irradiation effects and the birth of massive neutron stars3–6. Black widow pulsar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The follow-up timing observations have revealed that M71E has an orbit period of 53 minutes (Pan et al 2023). Its short orbit period of 53 minutes breaks the previous record for the orbit period of 75 minutes for PSR J1653-0158 (Nieder et al 2020); no eclipses and significant orbital period changes have been detected yet (Pan et al 2023). The nature of this system is not well understood yet.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The follow-up timing observations have revealed that M71E has an orbit period of 53 minutes (Pan et al 2023). Its short orbit period of 53 minutes breaks the previous record for the orbit period of 75 minutes for PSR J1653-0158 (Nieder et al 2020); no eclipses and significant orbital period changes have been detected yet (Pan et al 2023). The nature of this system is not well understood yet.…”
Section: Introductionmentioning
confidence: 85%
“…The nature of this system is not well understood yet. This system was interpreted as an intermediate between redbacks and black widows by Pan et al (2023). Based on a low mass function of 2.3 × 10 −7 M e and the strikingly short orbital period in the range of UCXB orbital periods, here we discuss an alternative evolution scenario for this binary system, namely that it is a newly evolved descendant of a UCXB, as a complementary theory to Pan et al (2023).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…By analyzing the pulsar timing data from the Five-hundredmeter Aperture Spherical radio Telescope (FAST), Pan et al (2023;hereafter Pan23) find that M71E (aka, PSR J1953 +1844, discovered by Han et al 2021 in the field of GC M71) is an extraordinary noneclipsing spider pulsar, which has a record-breaking short orbital period of P = 53.3 minutes and a very small mass function of 2.3 × 10 −7 M e . Pan23ʼs analysis favors a stripped dwarf companion with M c = 0.047-0.097 M e , estimated by imposing mass-radius relations for brown dwarfs (BDs)/low-mass dwarfs (Burrows et al 1993) and restricting its radius within the Roche lobe radius (Eggleton 1983).…”
Section: Introductionmentioning
confidence: 99%